The role of culture in shaping women's entrepreneurship: Evidence from Sabah, Malaysia - Salmah Topimin; Irma Wani Othman; Haslinda Hasan; Siti Nor Bayaah Ahmad (Academic Inspired Network, 2021)
Women's social environments are shaped by various cultural elements that influence their behaviour and actions in the public sphere. As such, this paper explores how socio-cultural elements in women's social environments influence their entrepreneurial activities. In-depth interviews with ten women entrepreneurs in the West Coast of Sabah were conducted. Although some cultural factors appear to assist women in pursuing their entrepreneurial activities, this study found that the factors also inhibit women entrepreneurs from realising their full business potential. The findings reveal that socio-cultural factors influence the business decisions made by women entrepreneurs. It becomes apparent that the concept of gender appropriate behaviour has given impact on women’s businesses in several aspects: motivating factors, industry preferences and strong family commitment as well as patriarchal pressures on business. This paper concludes that socio-cultural factors are critical to understanding of women’s entrepreneurship, thus, adding to the body of knowledge about the impact of culture on women's entrepreneurship.